![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^2+3x+3y+xy=x^2+xy+3x+3y=x.\left(x+y\right)+3.\left(x+y\right)\) \(=\left(x+3\right)\left(x+y\right)\)
\(x^2+5x^2+6x=x^2+x+5x^2+5x=x\left(x+1\right)+5x\left(x+1\right)\) \(=\left(x+5x\right)\left(x+1\right)=6x\left(x+1\right)\)
a)\(x^2+3x+3y+xy\)
\(=x\left(x+y\right)+3\left(x+y\right)\)
\(=\left(x+3\right)\left(x+y\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1.
7x(2x-1)=14x2-7x
2
a. x2+2x=x(x+2)
b.x2-xy+3x-3y
=x(x-y)+3(x-y)
=(x+3)(x-y)
Câu 2:
1. 2x/2x-5 - 5/2x-5
=2x-5/2x-5
=1
2. (6x3-7x2-x+2) : (x-1)=6x2-x-2
![](https://rs.olm.vn/images/avt/0.png?1311)
a/ \(=3y^2-6y-2x+1\)
b/ \(=-\left(x^3-3x^2+3x-1\right)=-\left(x-1\right)^3\)
c/ \(=\left(2-x\right)^3\)
d/ \(=xy^2+x^2y+3xy+x^2y+x^3+3x^2-3xy-3x^2-9x\)
\(=xy\left(y+x+3\right)+x^2\left(y+x+3\right)-3x\left(y+x+3\right)\)
\(=\left(xy+x^2-3x\right)\left(y+x+3\right)=x\left(y+x-3\right)\left(y+x+3\right)\)
e/ \(=xy-x^2+2x-y^2+xy-2y\)
\(=x\left(y-x+2\right)-y\left(y-x+2\right)=\left(x-y\right)\left(y-x+2\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) =(2x+3y-1)2
b)=-(x-1)3
c)=-(x3-6x2+12x-8)=-(x-2)3
d)x3 + 2x2y + xy2 – 9x
= x(x2 + 2xy + y2 -9)
= x[(x2 + 2xy + y2) - 32]
= x[(x + y)2 - 32]
= x (x + y – 3)(x + y + 3)
e) 2x-2y-x2+2xy-y2=2(x-y)-(x-y)2=(x-y)(2-x+y)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 6x2 - 11x + 3
= 6x2 - 9x - 2x + 3
= 3x ( 2x - 3 ) - ( 2x - 3 )
= ( 2x - 3 ) ( 3x - 1 )
b ) 2x2 + 3x - 27
= 2x2 - 6x + 9x - 27
= 2x ( x - 3 ) + 9 ( x - 3 )
= ( x - 3 ) ( 2x + 9 )
c ) 2x2 - 5xy - 3y2
= 2x2 - 2xy - 3xy - 3y2
= 2x ( x - y ) - 3y ( x - y )
= ( x - y ) ( 2x - 3y )
Ta có:
a) 6x2 - 11x +3 = 2x(3x-1)-3(3x-1)=(2x-3)(3x-1)
b) 2x2 +3x - 27= x(2x+9)-3(2x+9)=(x-3)(2x+9)
c) 2x2 -5xy-3y2 = 2x(x-3y)+y(x-3y)=(2x+y)(x-3y)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(xy^2-16x-48y+3y^2\)
\(=x\left(y^2-16\right)+3\left(y^2-16\right)\)
\(=\left(x+3\right)\left(y+4\right)\left(y-4\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a. \(2a^2+5ab-3b^2-7b-2\)
\(=\left(2a^2+6ab+2a\right)-\left(ab+3b^2+b\right)-\left(2a+6b+2\right)\)
\(=2a\left(a+3b+1\right)-b\left(a+3b+1\right)-2\left(a+3b+1\right)\)
\(=\left(2a-b-2\right)\left(a+3b+1\right)\)
b. \(2x^2-7xy+x+3y^2-3y\)
\(=\left(2x^2-xy\right)-\left(6xy-3y^2\right)+\left(x-3y\right)\)
\(=x\left(2x-y\right)-3y\left(2x-y\right)+\left(x-3y\right)\)
\(=\left(x-3y\right)\left(2x-y\right)+\left(x-3y\right)\)
\(=\left(x-3y\right)\left(2x-y+1\right)\)
c. \(6x^2-xy-2y^2+3x-2y\)
\(=\left(6x^2+3xy\right)-\left(4xy-2y^2\right)+\left(3x-2y\right)\)
\(=3x\left(2x+y\right)-2y\left(2x+y\right)+\left(3x-2y\right)\)
\(=\left(3x-2y\right)\left(2x+y\right)+\left(3x-2y\right)\)
\(=\left(3x-2y\right)\left(2x+y+1\right)\)
= 2x(x-3) + y (x-3)
= (2x+y)(x-3)
\(2x^2-6x+xy-3y=\left(2x^2-6x\right)+\left(xy-3y\right)=2x\left(x-3\right)+y\left(x-3\right)=\left(x-3\right)\left(2x+y\right)\)